2020
DOI: 10.1242/dev.183186
|View full text |Cite
|
Sign up to set email alerts
|

Wnt ligands regulate the asymmetric divisions of neuronal progenitors in C. elegans embryos

Abstract: Wnt/β-catenin signaling has been implicated in the terminal asymmetric divisions of neuronal progenitors in vertebrates and invertebrates. However, the role of Wnt ligands in this process remains poorly characterized. Here we used the terminal divisions of the embryonic neuronal progenitors in C. elegans to characterize the role of Wnt ligands during this process focusing on a lineage that produces the cholinergic interneuron AIY. We observed that during interphase the neuronal progenitor is elongated along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Thus, we propose that the Wnt signaling pathway has an instructive, rather than a permissive role on K-to-DVB Td, with WNT ligands acting as positional cues in this process, instructing which K daughter will cease to be a rectal cell. An analogous situation has been recently demonstrated in the SMDD/AIY asymmetric cell division during embryonic development (Kaur et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
“…Thus, we propose that the Wnt signaling pathway has an instructive, rather than a permissive role on K-to-DVB Td, with WNT ligands acting as positional cues in this process, instructing which K daughter will cease to be a rectal cell. An analogous situation has been recently demonstrated in the SMDD/AIY asymmetric cell division during embryonic development (Kaur et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
“…Wnt ligands bind receptor Fzd, alongside co-receptors Lrp5 or Lrp6, ultimately leading to β-catenin-dependent transcription of target genes. In several systems ( Bertrand, 2016 ; Goldstein et al, 2006 ; Huang and Niehrs, 2014 ; Kaur et al, 2020 ; Sugioka et al, 2011 ; Walston et al, 2004 ), including mouse embryonic stem cells (ESCs) ( Habib et al, 2013 ), localised Wnts induce oriented asymmetric cell division (ACD).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been established that for the endomesoderm precursor cell EMS or the larval blast cell T, Wnt ligands, secreted from a posterior source, control the division orientation and the asymmetry of daughter cell fates (Goldstein, Takeshita, Mizumoto, & Sawa, 2006). Interestingly, it has been recently observed that three Wnt ligands (CWN-1, CWN-2 and MOM-2), coming from the posterior of the embryo, regulate in an instructive manner the terminal asymmetric divisions of embryonic neuronal progenitors (Kaur et al, 2020). This illustrates the importance of intercellular signaling during neuronal development in C. elegans.…”
Section: Neuronal Specification: a Combination Of Lineage Inheritance And Intercellular Signalingmentioning
confidence: 99%